Aging and Neurodegenerative Disease: Is the Adaptive Immune System a Friend or Foe? - Mayne, Katie; White, Jessica A.; McMurran, Christopher E.; Rivera, Francisco J.; de la Fuente, Alerie G. (Frontiers in Aging Neuroscience, 2020)
Neurodegenerative diseases of the central nervous system (CNS) are characterised by progressive neuronal death and neurological dysfunction, leading to increased disability and a loss of cognitive function. Alzheimer’s disease, Parkinson’s disease and amyotrophic lateral sclerosis have neurodegeneration as a primary feature. However, in other CNS diseases such as multiple sclerosis, stroke, traumatic brain injury and spinal cord injury, neurodegeneration follows another insult, such as demyelination or ischaemia. Although there are different primary causes to these diseases, they all share a hallmark of neuroinflammation. Neuroinflammation can occur through the activation of resident immune cells such as microglia, cells of the innate and adaptive peripheral immune system, meningeal inflammation and autoantibodies directed towards components of the CNS. Despite chronic inflammation being pathogenic in these diseases, local inflammation after insult can also promote endogenous regenerative processes in the CNS, which are key to slowing disease progression. The normal ageing process in the healthy brain is associated with a decline in physiological function, a steady increase in levels of neuroinflammation, brain shrinkage and memory deficits. Likewise, ageing is also a key contributor to the progression and exacerbation of neurodegenerative diseases. As there are associated co-morbidities within an ageing population, pinpointing the precise relationship between ageing and neurodegenerative disease progression can be a challenge. The CNS has historically been considered an isolated, “immune privileged” site, however there is mounting evidence that adaptive immune cells are present in the CNS of both healthy individuals and diseased patients. Adaptive immune cells have also been implicated in both the degeneration and regeneration of the CNS. In this review, we will discuss the key role of the adaptive immune system in CNS degeneration and regeneration, with a focus on how ageing influences this crosstalk.